Penentuan Status Pemanfaatan dan Pengelolaan Ikan Tongkol (Auxis rochei) yang Tertangkap di Perairan Bolaang-Mongondow Selatan dan Bolaang-Mongondow Timur Sulawesi Utara - Ladi Beatriex Deeng; Hanny A H Komalig; John S Kekenusa (Sam Ratulangi University, 2020)
LADI BEATRIEX DEENG. Determination of Utilization and Management Status of Bonito (Auxis Rochei) Caught in South Bolaang-Mongondow and East Bolaang-Mongondow Waters of North Sulawesi. Supervised by Mr. JOHN S. KEKENUSA as main supervisor, and Mr. HANNY A. H. KOMALIG as co-supervisor.Bonito (Auxis rochei), needs to be managed properly because even though it is a renewable biological resource, it can experience overfishing, depletion or extinction. One way to approach the management of fish resources is by modeling. The analysis was carried out aiming to determine the status of utilization and management of bonito and maximum sustainable yield (MSY) using the Surplus Production Model. Data on catching and efforts to catch bonito is collected from the Marine and Fisheries Service of South Bolaang-Mongondow Regency and East Bolaang-Mongondow of North Sulawesi. The surplus production model that can be used to determine the catch of bonito is the Schaefer model. The maximum sustainable catch of bonito is 869.556 tons per year, obtained at the level of catching effort of 933 trips. For 2017 the level of utilization is 64.95 % so that production can still be increased, with a level of effort of 73.74 % indicating the level of effort that is not optimal and can still be increased.Â Keywords : Bonito, Surplus Production Model, South Bolaang-Mongondow andÂ Â East Bolaang-Mongondow Regency